2022
DOI: 10.1021/acs.jpclett.2c03437
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-Bandwidth Blue-Emitting Ag–Ga–Zn–S Semiconductor Nanocrystals for Quantum-Dot Light-Emitting Diodes

Abstract: I–III–VI type semiconductor nanocrystals (NCs) have attracted considerable attention in the display field. Herein, we realized the synthesis of narrow-bandwidth blue-emitting Ag–Ga–Zn–S (AGZS) NCs via a facile one-pot method. Intriguingly, the Ag/Zn feeding ratio and Ag/Ga feeding ratio are crucial for the realization of narrow-bandwidth AGZS NCs. By choosing a Ag/Zn feeding ratio of 4:1 and Ag/Ga feeding ratio of 1:8, AGZS NCs demonstrate a typical blue emission at 470 nm with a narrow full width at half-maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Tang et al reported the narrowest blue QLEDs (48 nm) based on Ag−Ga−Zn−S QDs (Figure 4d), the ratios of cations (Ag + /Zn 2+ and Ag + /Ga 3+ ) are the crucial for narrow emission. 26 This research provides a feasible strategy for pure-monochrome emission. Tsuzuki et al reported a GaS x -passivated AIGS QD, whose defect sites are compensated, and the defect-related direct electron injection are suppressed.…”
Section: ■ Synthesis and Optical Propertiesmentioning
confidence: 97%
See 3 more Smart Citations
“…Tang et al reported the narrowest blue QLEDs (48 nm) based on Ag−Ga−Zn−S QDs (Figure 4d), the ratios of cations (Ag + /Zn 2+ and Ag + /Ga 3+ ) are the crucial for narrow emission. 26 This research provides a feasible strategy for pure-monochrome emission. Tsuzuki et al reported a GaS x -passivated AIGS QD, whose defect sites are compensated, and the defect-related direct electron injection are suppressed.…”
Section: ■ Synthesis and Optical Propertiesmentioning
confidence: 97%
“…Copyright 2017 Royal Society of Chemistry. (d)–(f) EL spectra of blue, green, and red QDs, and the photographs demonstrate the LEDs under voltages. ,, Adapted with permission from ref (copyright 2022 American Chemical Society), ref (copyright 2018 The Optical Society of American, under CC BY 4.0), and ref (copyright 2023 American Chemical Society).…”
Section: Led Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ternary I-III-VI semiconductor nanocrystals or quantum dots (QDs), such as copper indium selenide QDs, have become attractive alternatives to the more well-established Cd-, Pb-, or Hg-containing QDs for in vivo applications. [7][8][9][10][11][12] Apart from their good biocompatibility due to the absence of highly toxic elements, their relatively narrow bulk band gaps allow the tuning of photoluminescence from the visible region all the way up to the near-infrared (NIR) spectral region, [13][14][15][16][17][18][19] where penetration through biological tissue is favorable. [20][21][22][23][24] In contrast to binary Cd-free QDs, ternary QDs show compositiondependent optical properties while maintaining similar particle sizes, which endows the QDs with analogous pharmacokinetic behaviors in vivo.…”
Section: Introductionmentioning
confidence: 99%